Increased anxiety and stress-related visits to the Shanghai psychiatric emergency department during the COVID-19 pandemic in 2020 compared to 2018–2019 - Zhang, TianHong; Chen, Zheng; Xiao, XuDong; Zhou, LinLin; Hu, YeGang; Xu, LiHua; Wei, YanYan; Tang, XiaoChen; Liu, HaiChun; Chen, Tao; Wu, HaiSu; Wu, XuMing; et al. (Frontiers in Psychiatry, 2023)
Background: The coronavirus disease 2019 (COVID-19) pandemic has had a significant and far-reaching impact on mental health. The psychiatric emergency department (PED) is pivotal in the management of acute and severe mental illnesses, especially anxiety- and stress-related disorders. Aims: This study aimed to evaluate whether changes in the frequency or patients’ demographics of visiting the psychiatric emergency department (PED) occurred during the coronavirus disease 2019 (COVID-19) pandemic among individuals with anxiety and stress-related disorders. Methods: This cross-sectional study used data on PED visit counts from the largest psychiatric hospital in China between 2018 and 2020 (before and during the COVID-19 pandemic). Data from 2020, representing the COVID-19 pandemic period, were extracted from electronic medical records and compared using descriptive statistics for the same periods in 2018 and 2019. Results: The number of PED visits related to anxiety and stress disorders per year increased from 83 in 2018 to 136 (63.9% increase) in 2019 and 239 (188.0% increase) in 2020. Compared to that in 2018 and 2019, the proportion of PED visits in 2020 among patients with anxiety and stress disorders increased significantly. Patients with anxiety- and stress-related disorders during PED visits in 2020 were younger than those in 2018 and 2019. Conclusions: Despite the epidemic-policy barriers against PED visits, PED care seeking has increased, thereby underscoring the need for crisis prevention services for patients with stress and anxiety disorders.